2018
DOI: 10.1021/acsami.7b16167
|View full text |Cite
|
Sign up to set email alerts
|

Ni2P Entwined by Graphite Layers as a Low-Pt Electrocatalyst in Acidic Media for Oxygen Reduction

Abstract: A simple and feasible strategy was reported to construct NiP nanostructures entwined by graphite layers (NiP/GC). In this process, a commercial amino phosphonic acid chelating resin was adopted as both the phosphorus and carbon resources. Then, Ni was introduced into the resin framework via ionic exchange and chelation to form a resin-Ni precursor. After carbonization, the highly dispersed NiP particles, coupled with thin graphite layers, were simultaneously synthesized in situ. A ternary 7.5% Pt-NiP/GC cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 68 publications
3
25
0
Order By: Relevance
“…Compared with Ni−P‐MOFs, when carbonization was proceeded at 773 K, there was change at the positions where peaks occurred in the crystalline diffraction peak of the sample, and the intensity of the diffraction peak was weakened. When carbonization temperature rose to 873 K, diffraction peaks of Ni−P‐MOFs disappeared, and diffraction peaks of Ni 2 P appeared at 2θ=40.6°, 44.6°, 47.3° and 54.1°, which were respectively corresponding to crystal faces (111), (210), (210) and (300), meanwhile a wide dispersion peak occurred near 25°, which belonged to amorphous carbon, it indicated that carbon‐covering Ni 2 P could be formed through carbonization treatment of Ni−P‐MOFs at 873 K under the nitrogen atmosphere, and with the increase of carbonization temperature, intensity of crystalline‐state diffraction peak of Ni 2 P was further strengthened.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with Ni−P‐MOFs, when carbonization was proceeded at 773 K, there was change at the positions where peaks occurred in the crystalline diffraction peak of the sample, and the intensity of the diffraction peak was weakened. When carbonization temperature rose to 873 K, diffraction peaks of Ni−P‐MOFs disappeared, and diffraction peaks of Ni 2 P appeared at 2θ=40.6°, 44.6°, 47.3° and 54.1°, which were respectively corresponding to crystal faces (111), (210), (210) and (300), meanwhile a wide dispersion peak occurred near 25°, which belonged to amorphous carbon, it indicated that carbon‐covering Ni 2 P could be formed through carbonization treatment of Ni−P‐MOFs at 873 K under the nitrogen atmosphere, and with the increase of carbonization temperature, intensity of crystalline‐state diffraction peak of Ni 2 P was further strengthened.…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35] Besides the structure aspect, composition optimization of Pt-based catalysts could potentially tailor the electronic structure of Pt atoms and adjustt heir adsorption/desorption properties toward catalytic reactants and products, and thus enhancet he activity of reactive sites. [36][37][38][39] In this regard, av ariety of Pt-based tri-metallic or multi-metallic nanomaterials have been reported and demonstrated their enhanced catalytic performance for DMFCs. [40][41][42][43] Despite these advances, the facile fabrication of Pt-based multi-metallic hollow nanostructures with well-defined open pore surfaces is less reportedd ue to the daunting challengei nm ultiscale structural and compositional control.…”
Section: Introductionmentioning
confidence: 99%
“…Among various structures, Pt‐based hollow nanostructures with well‐defined porous surfaces have been demonstrated their superiority in catalysis applications owing to their highly accessible surface areas, rich exposed reactive sites, and abundant mass diffusion pathways . Besides the structure aspect, composition optimization of Pt‐based catalysts could potentially tailor the electronic structure of Pt atoms and adjust their adsorption/desorption properties toward catalytic reactants and products, and thus enhance the activity of reactive sites . In this regard, a variety of Pt‐based tri‐metallic or multi‐metallic nanomaterials have been reported and demonstrated their enhanced catalytic performance for DMFCs .…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the Pt@Te-PsS catalyst with the Pt loading of only 1.08 wt % exhibits extremely outstanding electrocatalytic hydrogen evolution reaction activity. [18][19][20][21][22][23][24] The hierarchical nanostructures can also be utilized as templates to effectively reduce the loading of the precious metal, and the stability of catalysts can be greatly improved by inert template. [1][2][3] As benchmark electrocatalysts, precious metal-based catalysts have been proved to be the most efficient catalysts.…”
mentioning
confidence: 99%
“…[9][10][11][12] Therefore, the highly efficient utilization of precious metal is significantly important. [18][19][20][21][22][23][24] The hierarchical nanostructures can also be utilized as templates to effectively reduce the loading of the precious metal, and the stability of catalysts can be greatly improved by inert template. For example, the construction of coreshell structure just need to develop a ultra-thin precious metal shells on metal or non-metal cores.…”
mentioning
confidence: 99%